Evaluating Conservation Easement and Land Records Data in Rapidly Growing Counties in the United States and the Implications for Environmental Governance. Issue 2 (1st February 2022) - Overby, Anna Treado; Dyckman, Caitlin S.; Ogletree, Scott; Fouch, Nakisha; Lauria, Mickey; White, David L.; Baldwin, Robert F.; Amidon, Katherine; Crum, Daniel
Abstract: In the US, land records are fragmented and difficult to assemble. This paper details issues of access to land records from traditional land record institutions within US counties, focusing on conservation easements (CEs), CE geospatial data, and tax-assessment data. This paper also explores the issue of privacy related to CE land records and land trusts, the primary type of non-profit that holds CEs. Previous literature has cited landowner concerns about privacy as a driving force behind land trust's hesitancies to share information. However, we find evidence that landowner privacy concerns may be overestimated and more nuanced than previously reported. Additionally, we document widespread issues related to access of CE documents from register of deed's offices. This paper supports reforms to better track CEs within register of deeds offices and reforms to make land records data more accessible for pluralistic societal needs and to support inclusion in environmental governance.